PENGARUH PENGGUNAAN TEKNIK THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS 11 SMP NEGERI 11 PADANG - Sari, Uci Permata; R., Syahrul; Gani, Erizal (Universitas Negeri Padang, 2018)
ABSTRACTThe purpose of this study there are three. First, describe the skills of writing fable text of grade VII students of SMP Negeri 11 Padang before using Think Talk Write (TTW) technique. Second, describe the skills of writing fable text of grade VII students of SMP Negeri 11 Padang after using Think Talk Write (TTW) technique. Third, analyze the influence of Think Talk Write (TTW) technique to the writing skill of fable text of grade VII students of SMP Negeri 11 Padang.Kata kunci: pengaruh, teknik think talk write, teks fabel